Proses Lyriques in Context - Dworak, Paul (Revue musicale OICRM, 2014)
In Proses lyriques, Debussy developed new methods for setting text to music. The music critics in Paris and Brussels who reviewed this composition between 1894 and 1914 were in most cases highly critical of the work. Rather than admitting that they did not understand the goals that Debussy had set for this composition, some of the critics spoke of it in derogatory terms because they believed that it abandoned traditional principles for writing poetry and for setting the text to music. Debussy wrote the text for the four songs of Proses lyriques. He used the innovations in writing verse that were begun by Charles Baudelaire and culminated in works of Stéphane Mallarmé. In particular, Debussy used the literary genre of prose lyrique that was cultivated by the Belgian writer Arnold Goffin and some of his contemporaries. Prose lyrique was a synthesis of poésie lyrique and developments in vers libre that were prominent in poèmes en prose. Mallarmé and Remy de Gourmont, in particular, encouraged writers to be aware of the harmonic and rhythmic aspects of the words that they selected in their verse. This article presents selected reviews of Proses lyriques written during the two decades after its composition. It also discusses the development of verse during the second half of the 19th century. This discussion provides a context for understanding both the artistic environment in which Debussy composed these songs and the innovations that he implemented in this composition, so that future scholarship can explore his innovations in the design of his verse, its rhythm and word selection, and its melodic and harmonic realization.